Medical image archiving, processing, analysis and communication system for teleradiology - Suapang, Piyamas; Dejhan, Kobchai; Yimmun, Surapun (My University, 2010)
The design and implementation of Medical Image Archiving, Processing, Analysis and Communication System for Teleradiology which DICOM server was developed using software such as Borland Delphi 6.0, PHP and MySQL for image archive, image compression, image processing, image analysis and image transmission. The system provides the following facilities: (1) DICOM-format image archive. (2) Medical Image Compression. (3) DICOM viewer and Image processing, and (4) Image analysis. The results shown that (1) our system can also convert the image data both single frame and multiframes in normal or automatic DICOM process into the standard DICOM 3.0 format without altering the image data. (2) The resulting images are then compressed with two different techniques-JPEG and JPEG2000. The significant advantage of JPEG2000 over normal JPEG is that the error from JPEG2000 compression is smaller than the error from JPEG. Nevertheless, both methods share a similar mishap; when the compression ratio increases, they both generate more error than the processes on lower compression ratio. (3) our system can open single frame and multiframes such as DICOM, INTERFILE, BITMAP, JPEG and JPEG2000 each of which can exhibit information in. dcm file format with no distortion and image processing which has also the capabilities to zoom in/out and contrast/color map. And, (4) Image analysis sets ROI semi-automatically on region of expected disease based on geometric active contour model from edge of variance image and Canny edge detection. Thence, our system can calculate of Glomerular Filtration Rate (GFR), Effective Renal Plasma Flow (ERPF), and plot of the Time Activity Curve or Renogram The system has been developed and provided medical image services over long distance which showed the usefulness of our approach. ©2010 IEEE.
Keywords: Image analysis; Image archiving; Image compression; Image processing; Teleradiology